Pressure induced manifold enhancement of Li-kinetics in FCC fullerene - Das, Deya; Han, Sang Soo; Lee, Kwang-Ryeol; Singh, Abhishek K. (ROYAL SOC CHEMISTRY, 2014)
The reduction of the diffusion energy barrier for Li in electrodes is one of the required criteria to achieve better performances in Li ion batteries. Using density functional theory based calculations, we report a pressure induced manifold enhancement of Li-kinetics in bulk FCC fullerene. Scanning of the potential energy surface reveals a diffusion path with a low energy barrier of 0.62 eV, which reduces further under the application of hydrostatic pressure. The pressure induced reduction in the diffusion barrier continues till a uniform volume strain of 17.7% is reached. Further enhancement of strain increases the barrier due to the repulsion caused by C-C bond formation between two neighbouring fullerenes. The decrease in the barrier is attributed to the combined effect of charge transfer triggered by the enhanced interaction of Li with the fullerene as well as the change in profile of the local potential, which becomes more attractive for Li. The lowering of the barrier leads to an enhancement of two orders of magnitude in Li diffusivity at room temperature making pressurized bulk fullerene a promising artificial solid electrolyte interface (SEI) for a faster rechargeable battery.
Keywords: SILICON THIN-FILM; HIGH-CAPACITY; SINGLE-LAYER; LITHIUM; C-60; ION; BATTERY; CHALLENGES; DIFFUSION; ANODES